Insertion of the values of religious moderation on Indonesian EFL class - Ida Fitri Anggarini (Journal of English Language Teaching and Learning (JETLE), 2022)
English as a Foreign Language (EFL) means learning English in a non-English speaking country, for example, Thailand and Indonesia. Admittedly, EFL educators encourage the student to improve their English skills such as listening, speaking, reading, and writing skills. In writing skills, teaching vocabulary has important points. Focusing on learning English vocabulary that inserts the value of religious moderation, this research took a case study in an Islamic primary school in Malang on Indonesian EFL Class. With a qualitative case study, the researcher addressed two main methods for two Indonesian EFL students and teachers in Malang. By using reflective essays and interviews as the methods, the data concluded that most of the challenges found had similarities and related to each other. Along with the challenges, the researcher also found out the strategies done by all of the participants such as implementing the values of religious moderation as a way of teaching vocabulary, enriching the student’s vocabulary, and improving the student’s writing English skills.